2017
DOI: 10.5812/zjrms.7210
|View full text |Cite
|
Sign up to set email alerts
|

Camellia Sinensis Modulates Telomerase in Collagen-Induced Arthritis

Abstract: Background: Rheumatoid arthritis is a chronic inflammatory disease with undefined pathogenesis. Some evidence suggests that telomerase is involved in the pathogenesis of this disease. This study was done to evaluate the therapeutic potency of Camellia sinensis stew (CSS) which rich in polyphenolic compounds with anti-inflammatory properties in experimental model of rheumatoid arthritis. Methods: In this experimental study, collagen-induced arthritis (CIA) was induced by immunization of Lewis rats. The paws and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The data showed that green tea reduced paw edema, bone erosion, and inflammatory responses in joints of treated rats. It also reduced telomerase activity in comparison with the control group [62].…”
Section: Camellia Sinensis (Green Tea)mentioning
confidence: 80%
“…The data showed that green tea reduced paw edema, bone erosion, and inflammatory responses in joints of treated rats. It also reduced telomerase activity in comparison with the control group [62].…”
Section: Camellia Sinensis (Green Tea)mentioning
confidence: 80%